Kesulitan Siswa Memahami Konsep Penentuan Perubahan Entalpi Reaksi di Kelas XI-MIPA SMA Tahun Ajaran 2022/2023 Menggunakan Tes Diagnostik Berbentuk Uraian - Helda Yanti; Sidauruk, Suandi; Asi, Nopriawan Berkat (FKIP Universitas Palangka Raya, 2024)
Education in Indonesia aims to produce excellent students capable of contributing to the nation's progress. However, many schools still struggle to achieve an ideal level of learning, one of the contributing factors being the learning difficulties experienced by students. Chemistry is often perceived as a difficult subject due to its abstract and complex concepts. Determining reaction enthalpy changes in thermochemistry is one of the subtopics that students find challenging, leading to learning difficulties at the high school level. This issue is crucial to understand because chemistry concepts are interconnected, and difficulties in one area can affect the understanding of subsequent concepts. Hence, a study on students' difficulties in understanding the concept of determining reaction enthalpy changes is essential. This research was conducted on 125 Grade XI-MIPA students from two high schools in Palangka Raya. Data on students’ difficulties were collected using a diagnostic essay test instrument on the ability to determine reaction enthalpy changes (TKPPER), consisting of four questions. The aim of this research was to describe the difficulties experienced by Grade XI-MIPA students in the 2022/2023 academic year in understanding the concept of determining reaction enthalpy changes using diagnostic essay tests. The results showed that students experienced difficulties in understanding the concept of determining reaction enthalpy changes, with an average difficulty percentage of 37.44%. Several conceptual indicators focused on in the study exhibited varying levels of difficulty: Determining reaction enthalpy changes based on Hess's Law (65.67%), with students facing the following difficulties: (a) Assuming it is sufficient to sum the enthalpy change values (∆H) of three reactions provided in the question without considering the thermochemical equations of these reactions. (b) Believing that the value and sign of ∆H remain the same even when the thermochemical equation is reversed or the roles of reactants and products are switched. Determining reaction enthalpy changes based on bond energy (43.90%), with students experiencing the following issues: (a) Assuming that some compounds involved in the reactants and products are treated as single compounds in the chemical reaction. (b) Simply summing the bond energy values of each compound in the products and reactants without considering the number of bonds in each compound. Determining reaction enthalpy changes based on standard enthalpy change data (20.38%), with students facing the following challenges: (a) Assuming that the reactants in a chemical reaction are the products and vice versa. (b) Believing that it is sufficient to sum the bond energy values of each compound involved without accounting for the number of compounds (stoichiometric coefficients) in the reaction. Determining reaction enthalpy changes based on calorimeter experiment data (19.82%), where students struggled with identifying the values of the components in the formula, specifically determining the mass of water (m), specific heat capacity of water (c), and temperature change (∆T).